Biometric identification system - Garg, Amulya (2014)
In today's world, most of the daily routine processes are moving towards digitalisation and automation. For most of the systems assisting in this transition, their security is based heavily on validation routines which utilise information to identify and give access to the client. But these methods prove insufficient in the current times. Most of the identification is carried out either through a physical token or through remembered information. But physical identification is easy to replicate and the remembered information has high chances of being forgotten or being cracked. This leads to the high chances of unauthorised access to the system. Hence the interest for a more dependable security framework to protect sensitive data. The answer to all the above is security based on Biometric Identification.